Absorption of heavy metals and dyes from textile wastewater by using eggshell / Nur Farhana Azhar - Azhar, Nur Farhana (2017)
Introduction: Textile industry is known as one of the generators that produced a large amount of wastewater pollutants due to the large quantities of water consumed during fabric processing. Objective: The objectives of this study is to investigate the potential of eggshells as adsorbent for removal of pollutants from the textile industry wastewater without treatment. Methodology: The wastewater sampling at the selected area was conducted including in-situ and ex-situ sampling to identify the characteristics of the wastewater and compare the sample with Environmental Quality (Sewage and Industrial Effluent) Regulations 1974. Therefore, alternative treatment such as adsorption was investigated. The efficiency of eggshell as the adsorbent are really effective and able to remove the heavy metals (Pb, Zn, Mn and Cu) and dyes concentration in a large amount. Result: Based on the result, the wastewater does have a high reading of turbidity, high concentrations of BOD and COD, highly coloured effluents and heavy metals. All the characteristics of textile wastewater violated the permissible limit standard stated by the Environmental Quality (Sewage and Industrial Effluent) Regulations 1974. The optimum condition in the removal of heavy metals and dyes was obtained. As for lead (Pb) and copper (Cu) show the highest percentages of removal up to 100% followed by the manganese (Mn) and zinc (Zn) which is 91% and 62% respectively. Meanwhile, the removal percentages for the dyes is 80% Conclusion: This study concluded that the textile wastewater containing high concentrations of pollutant including the heavy metals and dyes.